Biological therapy for paediatric IBD – effective but associated with financial and safety issues. (4th April 2011) - Cameron, F; Wilson, M; Basheer, N; Jamieson, A; Bisset, W M; Russell, R; Wilson, D
Abstract : Background: Biological agents are increasingly used as treatment for paediatric inflammatory bowel disease (PIBD) in the UK, but with a weak evidence base and rising safety concerns. We aimed to evaluate pattern of usage, effectiveness and safety in the clinical setting using a Scottish national framework. Methods: Usage of infliximab (IFX), adalimumab (ADA) and natalizumab (NAT) for treatment of PIBD (aged <18 years of age at start of biological therapy) from 1 January 2000 to 30 April 2010 was collated in a retrospective audit. Treatment was administered by members of the Scottish Society of Paediatric Gastroenterology, Hepatology and Nutrition. Results: 112 children had ≥1 biological agent administered from a median (range) age of 14.3 (6.6–17.9) years; 50 (45%) were female and 102 (91%) had Crohn's disease (CD), 8 (7%) had ulcerative colitis and 2 (2%) had IBD unclassified (IBDU). 22 (20%) had trials of 2 biological agents. 104 children (98 CD) had IFX, with a median (range) of 4 (1–25) infusions mostly with moderate-severe IBD. 38 entered remission, 34 responded, and 32 had no response. 11 of the 46 (24%) proceeding to maintenance IFX required escalation of therapy. 14 (13%) had infusion events with 3 having anaphylaxis, and 7 reactions led to discontinuation. 1 child developed a lupus-like reaction requiring prolonged hospitalisation and 1 had severe infection, with no deaths. 19 (18%) proceeded to ADA. 23 children (all CD) had ADA therapy (including 19 after IFX, 2 as first biological and 2 with inflammatory arthritis in whom CD developed on etanercept), with a median of 20 doses and most with moderate-severe IBD. 11 entered remission, 6 responded, and 6 had no response. All proceeded to maintenance; 11 (50%) required escalation of therapy. 13 had pain at injection site with none discontinuing. 1 child developed leucopaenia and 1 a severe viral infection, with no deaths. 2 children with CD had NAT, both in a trial, and both proceeded to IFX after the agent was withdrawn. Conclusions: Our nationwide 'real-life' experience shows that biological agents are effective in moderate-severe paediatric IBD in the clinical setting, but there are significant financial and safety issues.